2002
DOI: 10.1071/ar02044
|View full text |Cite
|
Sign up to set email alerts
|

Lodging reduces sucrose accumulation of sugarcane in the wet and dry tropics

Abstract: Previous experiments in the Australian tropics have observed a 'slowdown' in biomass accumulation in mature sugarcane crops. By installing scaffolding to prevent lodging, we eliminated the growth 'slowdown' in 3 experiments to confirm that lodging and stalk death are part of the explanation. In both the wet and dry (irrigated) tropics, lodging of sugarcane significantly decreased both fresh cane yield and commercial cane sugar content (CCS). Prevention of lodging increased cane yield by 11–15%, CCS by 3–12%, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
34
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 10 publications
1
34
0
Order By: Relevance
“…While pastures and forests can be reasonably resilient to wet conditions including waterlogging, sugarcane productivity is severely compromised by low radiation, and by submergence and lodging. A local impact of intense low-pressure systems, including cyclones, is the combination of intense rainfall and high wind speeds, which causes lodging and reduction of sugar content in sugarcane (Singh et al 2002) and, potentially, damage to plantation forests. Northern inland pasture systems are generally favoured by La Niña events (Park et al 2003) and could respond positively to climate change in terms of productivity, albeit with a need to buffer production between years of high and low rainfall (O'Reagain et al 2011).…”
Section: Systems Of Cultivated Plant Species and Relative Production mentioning
confidence: 99%
“…While pastures and forests can be reasonably resilient to wet conditions including waterlogging, sugarcane productivity is severely compromised by low radiation, and by submergence and lodging. A local impact of intense low-pressure systems, including cyclones, is the combination of intense rainfall and high wind speeds, which causes lodging and reduction of sugar content in sugarcane (Singh et al 2002) and, potentially, damage to plantation forests. Northern inland pasture systems are generally favoured by La Niña events (Park et al 2003) and could respond positively to climate change in terms of productivity, albeit with a need to buffer production between years of high and low rainfall (O'Reagain et al 2011).…”
Section: Systems Of Cultivated Plant Species and Relative Production mentioning
confidence: 99%
“…In experiments conducted in Australia, sugarcane crops were physically prevented from lodging by means of bamboo scaffolding (Singh et al, 2002). These experiments revealed that prevention of lodging resulted in 11 -15% and 15 -35% higher cane and sugar yields respectively.…”
mentioning
confidence: 99%
“…Lodging is known to reduce the productivity of sugarcane through lower biomass production and a reduction in cane quality (Muchow et al, 1995;Singh et al, 2002;. These effects are caused by a reduction in radiation interception, radiation use efficiency, stalk smothering, stalk death and stalk snapping in lodged crops (Muchow et al, 1995;Singh et al, 2002;Park et al, 2005).…”
mentioning
confidence: 99%
See 2 more Smart Citations